Pericytes: Intrinsic Transportation Engineers of the CNS Microcirculation - Eltanahy, Ahmed M.; Koluib, Yara A.; Gonzales, Albert (Frontiers in Physiology, 2021)
Pericytes are candidates to regulate microcirculatory blood flow because they are strategically positioned along the microvasculature, contain contractile proteins, respond rapidly to neuronal activation, and synchronize microvascular dynamics and neurovascular coupling within the capillary network. Analyzing mice that have defects in pericyte generation demonstrates that pericytes are necessary for the formation of the blood-brain barrier (BBB), immune homeostasis, glymphatic function, and white matter function. This, however, remains unclear: the identity, specialization, and progeny of different subtypes of pericytes. Pericytes can perform brain-wide civil engineering functions at the capillary network; being able to instruct, integrate and coordinate signals within the cellular communicome in the neurovascular unit. We review the literature to identify challenges emerging in pericyte biology and shed light on an its translational medicine and therapeutics approaches.